Conceptual Metaphors of Sin in Thai - Eakkapochana, Dhanaphon (Chophayom Journal, 2023)
The objective of this research was to analyze metaphorical expressions and conceptual metaphors associated with sin in Thai language according to cognitive linguistics. Data was collected from chat room in category of religion on Pantip website. The results found 158 metaphorical expressions revealed 5 conceptual metaphors of Thais; sin is a measurable matter, sin is plant, sin is sewage, sin is a disease and sin is fire. The results pointed that the conceptual systems of Thais which are considered as negative perspectives toward sin are bad things affecting to their ways of life. Keywords: Sin, Cognitive Linguistics, Metaphorical Expressions, Pantip Website, Conceptual Metaphor